Diminished met signaling in podocytes contributes to the development of podocytopenia in transplant glomerulopathy - Agustian, Putri A.; Schiffer, Mario; Gwinner, Wilfried; Schaefer, Irini; Theophile, Katharina; Modde, Friedrich; Bockmeyer, Clemens L.; Traeder, Jana; Lehmann, Ulrich; Grosshennig, Anika; Kreipe, Hans H.; Broecker, Verena; et al. (American Journal of Pathology, 2011)
Transplant glomerulopathy (TxG) can show secondary focal and segmental glomerulosclerosis (FSGS). FSGS in native kidneys is caused by podocytopenia. This study examines podocytopenia and the role of decreased paracrine Met activation on podocytes by decreased glomerular hepatocyte growth factor (HGF) levels in the development of podocytopenia in TxG. Podocytes were counted in 10 zero-hour biopsies and 10 specimens each with and without TxG. HGF/Met was examined with immunostains and quantitative RT-PCR in a set of three consecutive biopsies from 10 patients with TxG, including the diagnostic biopsy (DiagnBx) and the two previous biopsies (1stPrevBx and 2ndPrevBx). Antiapoptotic effects of HGF on podocytes were examined in vitro. Mean podocyte numbers per glomerulus were lower and glomerular volume higher in TxG. Fewer of the two preceding biopsies of the patients than of the controls contained phospho-Met-(Tyr1349)- positive podocytes (2 of 8 versus 7 of 7, P = 0.0070; 4 of 9 versus 9 of 9, P = 0.0294). Glomerular HGF mRNA levels were lower in the 1stPrevBx of the patients (0.049 ± 0.083 versus 0.284 ± 0.331; P = 0.0155). In vitro, HGF stimulation of podocytes resulted in antiapoptotic phosphorylation of AKT and extracellular signal-regulated kinase (ERK) and induction of X-linked inhibitor of apoptosis protein (XIAP). Decreased antiapoptotic Met signaling in podocytes, probably due to decreased HGF secretion by glomerular epithelial cells, could contribute to podocyte loss and FSGS in TxG. Copyright © 2011 American Society for Investigative Pathology. Published by Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2020-11-12